Cellulose nanocrystals modification by grafting from ring opening polymerization of a cyclic carbonate. (1st November 2022) - Lalanne-Tisné, Michael; Eyley, Samuel; De Winter, Julien; Favrelle-Huret, Audrey; Thielemans, Wim; Zinck, Philippe
Abstract: Surface modification of cellulose nanocrystals (CNC) by organocatalysed grafting from ring-opening polymerization (ROP) of trimethylene carbonate was investigated. Organocatalysts including an amidine (DBU), a guanidine (TBD), an amino-pyridine (DMAP) and a phosphazene (BEMP) were successfully assessed for this purpose, with performances in the order TBD > BEMP > DMAP, DBU. The grafting ratio can be tuned by varying the experimental parameters, with the highest grafting of 74 % by weight obtained under mild conditions, i.e at room temperature in tetrahydrofuran with a low amount of catalyst. This value is much higher than that of typical ring opening polymerizations of cyclic esters initiated from the surface of cellulose nanoparticles. Additionally, DSC analysis of the modified material revealed the presence of a glass transition temperature, indicative of a sufficient graft length to display polymeric behaviour. This is, to our knowledge, the first example of cellulose nanocrystals grafted with polycarbonate chains. Graphical abstract: Unlabelled Image